A requiem for the fiscal theory of the price level - Farmer, Roger E. A. (IMF working paper ;, 2019)
The Fiscal Theory of the Price Level (FTPL) is the claim that, in a popular class of theoretical models, the price level is sometimes determined by fiscal policy rather than monetary policy. The models where this claim has been established assume that all decisions are made by an infinitely-lived representative agent. We present an alternative, arguably more realistic model, populated by sixty-two generations of people. We calibrate our model to an income profile from U.S. data and we show that the FTPL breaks down. In our model, the price level and the real interest rate are indeterminate, even when monetary and fiscal policy are both active. Our findings challenge established views about what constitutes a good combination of fiscal and monetary policies.